Bacillus velezensis A2 Inhibited the Cecal Inflammation Induced by Zearalenone by Regulating Intestinal Flora and Short-Chain Fatty Acids - Cai, Jing; Wang, Nan; Chen, Jia; Wu, Aibo; Nepovimova, Eugenie; Valis, Martin; Long, Miao; Wu, Wenda; Kuca, Kamil (Frontiers in Nutrition, 2022)
Zearalenone (ZEA) as an estrogen-like mycotoxin can cause the inflammatory injury of the cecum. How to reduce the harm that ZEA causes to humans and animals is a current concern for researchers. In this study, we aimed to ascertain whether Bacillus velezensis A2 could alleviate injury caused by ZEA by regulating the intestinal flora and the content of SCFA in the cecum among mice. Our results showed that Bacillus velezensis A2 improved the fold height, myometrial thickness, and crypt depth of the cecum induced by ZEA. Enzyme-linked immunosorbent assay (ELISA) and Western blotting results showed that A2 could decrease the ZEA-induced increase in expression levels of IL-2, IL-6, IFN-γ, TNF-α, and FC. Studies also showed that A2 increased the content of SCFA in the cecum which was decreased by ZEA. The microbial communities in the cecum were changed when given ZEA or A2. A2 was found to greatly reduce the ZEN-induced increase in the relative abundance of p_Actinobacteria, p_Protebacteria, o_Coriobacteriales, g_Anaerotruncus, g_Pseudoflavonifractor, g_Lachnoclostridium, g_Enterorhabdus, and f_Oscillospiraceae, and increase the ZEN-induced decrease in the relative abundance of f_Coriobacteriales. Results indicated that Bacillus velezensis A2 can largely ameliorate the intestinal inflammatory injury induced by ZEA in mice by regulating the microflora and SCFA content.